THE CONCEPT OF GOD’S VICE-REGENT THROUGH AL-TSA’LABY AL-MAGHRIBY AL-MALIKI PERCEPTION ON JAWAHIR AL HISAAN COMMENTARY - Nawal, Ahmad Faidlun (jfpublisher, 2023)
There are many misconceptions about the concept of God's vice-regent in the true meaning. It concerns the initial concept that a word contains, which is one of several causes that result in a change of meaning. If this continues, it will give new meaning and make the meaning of the word no longer identified, or has disappeared. The objectives of this research are to find out the definition and characteristics of God's vice-regent according to Imam al-Tsa'laby al-Maghriby al-Maliki which he was famous for his guardianship in his time, and to find out Imam al-Tsa'laby's perception of God's vice-regent. In addition, to find the relevance and contextualization of Imam al-Tsa'laby al-Maghriby al-Maliki's thoughts that are studied in the current context. This research used a qualitative approach that is more descriptive and library research, and the data sources that researchers use are divided into two, (1) primary sources, Jawahir al-Hisaan commentary; (2) secondary sources, which are literature that supports primary data obtained from books related to God's vice-regent. The results of this research indicated that the basic principles in understanding the God's vice-regent are believers who have obedience and worship of God, and whoever believes and fears God, then he belongs to the God's vice-regent, and this is required by sharia in the vice-regent, who has no fear of the hereafter, and perhaps in this world, they do not fear anyone from the inhabitants of this world, nor from its symptoms, and they do not grieve for those they miss from it.